Neurodevelopmental phenotype in 36 new patients with 8p inverted duplication–deletion: Genotype–phenotype correlation for anomalies of the corpus callosum. Issue 3 (15th December 2021) - Vibert, Roseline; Mignot, Cyril; Keren, Boris; Chantot‐Bastaraud, Sandra; Portnoï, Marie‐France; Nouguès, Marie‐Christine; Moutard, Marie‐Laure; Faudet, Anne; Whalen, Sandra; Haye, Damien; Garel, Catherine; Chatron, Nicolas; et al.
Abstract: Inverted duplication deletion 8p [invdupdel(8p)] is a complex and rare chromosomal rearrangement that combines a distal deletion and an inverted interstitial duplication of the short arm of chromosome 8. Carrier patients usually have developmental delay and intellectual disability (ID), associated with various cerebral and extra‐cerebral malformations. Invdupdel(8p) is the most common recurrent chromosomal rearrangement in ID patients with anomalies of the corpus callosum (AnCC). Only a minority of invdupdel(8p) cases reported in the literature to date had both brain cerebral imaging and chromosomal microarray (CMA) with precise breakpoints of the rearrangements, making genotype–phenotype correlation studies for AnCC difficult. In this study, we report the clinical, radiological, and molecular data from 36 new invdupdel(8p) cases including three fetuses and five individuals from the same family, with breakpoints characterized by CMA. Among those, 97% ( n  = 32/33) of patients presented with mild to severe developmental delay/ID and 34% had seizures with mean age of onset of 3.9 years (2 months–9 years). Moreover, out of the 24 patients with brain MRI and 3 fetuses with neuropathology analysis, 63% ( n  = 17/27) had AnCC. We review additional data from 99 previously published patients with invdupdel(8p) and compare data of 17 patients from the literature with both CMA analysis and brain imaging to refine genotype–phenotype correlations for AnCC. This led us to refine a region of 5.1 Mb common to duplications of patients with AnCC and discuss potential candidate genes within this region. Abstract :